最高のコレクション 4x^2 12xy 9y^2 x=-2 y=2 286878
Algebra > Polynomialsandrationalexpressions> SOLUTION Factor the following 4x^212xy9y^2 2x^3x^232x 28y^313y6 8p^3q^9 x^6y^6 Log On Algebra Polynomials, rational expressions and equations Section
4x^2 12xy 9y^2 x=-2 y=2- 4x^29y^225z^212xy = (2x)^2 (3y)^22×2x×3y25z^2 = (2x3y)^2 (5y)^2 = (2x3y5z) (2x3y5z) Hope it will help u cliffffy4h and 199 more users found this answer helpful heart outlined Thanks 132 star4x squared minus 12xy plus 9y squared minus 26x minus 52y plus 10 equally 0;
4x^2 12xy 9y^2 x=-2 y=2のギャラリー
各画像をクリックすると、ダウンロードまたは拡大表示できます
![]() | ![]() | |
![]() | ![]() | |
![]() | ||
![]() | ||
「4x^2 12xy 9y^2 x=-2 y=2」の画像ギャラリー、詳細は各画像をクリックしてください。
![]() | ![]() | |
![]() | ![]() | |
![]() | ![]() | |
![]() | ![]() | ![]() |
「4x^2 12xy 9y^2 x=-2 y=2」の画像ギャラリー、詳細は各画像をクリックしてください。
![]() | ![]() | |
![]() | ![]() | |
![]() | ![]() | ![]() |
![]() | ![]() | ![]() |
「4x^2 12xy 9y^2 x=-2 y=2」の画像ギャラリー、詳細は各画像をクリックしてください。
![]() | ![]() | |
![]() | ![]() | ![]() |
![]() | ![]() | ![]() |
![]() | ![]() | |
「4x^2 12xy 9y^2 x=-2 y=2」の画像ギャラリー、詳細は各画像をクリックしてください。
![]() | ![]() | |
![]() | ![]() | |
![]() | ![]() | |
「4x^2 12xy 9y^2 x=-2 y=2」の画像ギャラリー、詳細は各画像をクリックしてください。
![]() | ![]() | |
![]() | ![]() | |
![]() | ![]() | |
![]() | ![]() | |
「4x^2 12xy 9y^2 x=-2 y=2」の画像ギャラリー、詳細は各画像をクリックしてください。
![]() | ![]() | ![]() |
![]() | ![]() | ![]() |
![]() | ![]() | ![]() |
![]() | ![]() | ![]() |
「4x^2 12xy 9y^2 x=-2 y=2」の画像ギャラリー、詳細は各画像をクリックしてください。
![]() | ![]() | |
![]() | ![]() | ![]() |
![]() | ||
![]() | ||
「4x^2 12xy 9y^2 x=-2 y=2」の画像ギャラリー、詳細は各画像をクリックしてください。
![]() | ![]() | |
![]() |
Solution for 4x^2y^22y=0 equation Simplifying 4x 2 y 2 2y = 0 Reorder the terms 4x 2 2y y 2 = 0 Solving 4x 2 2y y 2 = 0 Solving for variable 'x' Move all terms containing x to the left, all other terms to the right Add '2y' to each side of the equation 4x 2 2y 2y y 2 = 0 2y Combine like terms 2y 2y = 0 4x 2 0 y 2 = 0 2y 4x 2 y 2 = 0 2y Remove theSolution Steps 4 x ^ { 2 } y ^ { 2 } 12 x y 9 4 x 2 y 2 1 2 x y 9 Use the perfect square formula, a^ {2}2abb^ {2}=\left (ab\right)^ {2}, where a=2xy and b=3 Use the perfect square formula, a 2 2 a b b 2 = ( a b) 2, where a = 2 x y and b = 3 \left (2xy3\right)^ {2} (
コメント
コメントを投稿